A Detailed Study of Space X Vs. Blue Origin Vs. Virgin Galactic and the Future of Space Travel - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
Space travel has had a generally short history. Regardless of its recency, the field has seen quick improvement in recent years. When the area of legislatures, space travel is currently likewise confidential. Starting from the primary business of human space flight occurred in 2001; a few other well-off space vacationers bought their rides into space. Over 150 individuals have pursued sub-orbital space trips with Virgin Galactic. Be that as it may, there are critical hindrances in making space travel a reality for the overall population. The enormous three Space X, Blue Origin, and Virgin Galactic are as yet developing confidential space industry was established entirely by super business visionaries who rose to acclaim (and significant riches) through non-space undertakings. Each has entered the ring with the usual point of reforming space travel, yet in light of one-of-a-kind goals and various dreams regarding how to accomplish their missions. Assuming that one property is shared by the administrations of SpaceX, Blue Origin, and Virgin Galactic, it is the definition of aggressive objectives. Here is a gander at the expressed missions of these three spearheading organizations: 1. SpaceX's central goal to make "humankind multi-planetary" is well in progress and has the red planet Mars soundly in its sights with the reusable Starship rocket program as the essential stage 2. Blue Origin additionally embraces rocket reusability as vital to its primary goal to save the planet by taking advantage of the room's "limitless assets and energy," comparing the new time of room travel and investigation to the Industrial Revolution of the cutting-edge period. 3. Virgin Galactic's main goal to "democratize space" will rely to a great extent upon the outcome of its space travel industry model by which the world's most memorable space line (rather than a carrier) will offer standard "flights" to space from its Spaceport America in New Mexico.